2022
DOI: 10.1038/s41598-022-24295-2
|View full text |Cite
|
Sign up to set email alerts
|

Salivary secretory leukocyte protease inhibitor levels in patients with stage 3 grade C periodontitis: a comparative cross-sectional study

Abstract: Secretory leukocyte protease inhibitor (SLPI) is an anti-protease that protects mucosal tissue integrity owing to its anti-microbial and immunomodulatory properties. This study aimed to investigate SLPI levels in periodontal diseases, and analyze the potential correlation with clinical periodontal parameters. Whole saliva samples were obtained from healthy (n = 24), gingivitis (n = 24) and patients with stage 3 grade C periodontitis (n = 24). SLPI was measured by ELISA and normalized by total protein. Receiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Salivary antioxidant levels (SOD, GPx, reduced GHS, ascorbic acid, alfa tocopherol, were observed to the lower in periodontal patients (Canacki) [146,[155][156][157]. In the present study, sulfhydryl (thiol), in gingival tissue, was observed in reduced quantities in the patients with gingivitis and periodontitis (groups B and C), compared with the people from healthy group (Group A) [158,159]. Testing the significance of differences in the concentration of sulfhydryl (thiol) group between the examined groups by post hoc test showed statistically significant differences in the values of this parameter among all groups of patients (F: 138.91; p < 0.001; p = 0.000) [160].…”
Section: Discussionmentioning
confidence: 54%
“…Salivary antioxidant levels (SOD, GPx, reduced GHS, ascorbic acid, alfa tocopherol, were observed to the lower in periodontal patients (Canacki) [146,[155][156][157]. In the present study, sulfhydryl (thiol), in gingival tissue, was observed in reduced quantities in the patients with gingivitis and periodontitis (groups B and C), compared with the people from healthy group (Group A) [158,159]. Testing the significance of differences in the concentration of sulfhydryl (thiol) group between the examined groups by post hoc test showed statistically significant differences in the values of this parameter among all groups of patients (F: 138.91; p < 0.001; p = 0.000) [160].…”
Section: Discussionmentioning
confidence: 54%
“…Early-stage periodontal disease, gingivitis, is characterised by red and swollen gums. In some individuals, bacteria in the gingival biofilm secrete an excess of proteases that affect surrounding tissues [6]. An immune response is then likely to trigger the recruitment of inflammatory response units such as cytokines and matrix metalloproteases.…”
Section: Introductionmentioning
confidence: 99%